Will thrombopoietin receptor agonists become a treatment option for pediatric chronic immune thrombocytopenia in the future?. (March 2015) - Cheng, Gregory
Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by a low platelet count and increased bleeding tendency. Most children with ITP spontaneously recover. However, children with severe bleeding may require treatment. Traditional treatments such as corticosteroids or splenectomy are often associated with increased risks of infections. Currently, there is evidence that platelet production is suboptimal in many chronic ITP patients and stimulation of platelet production by thrombopoietin receptor agonists (TpoR-As) is effective in raising the platelet counts. However, these clinical studies were conducted mainly in chronic ITP patients, age 18 or above, and TpoR-As are not yet licensed for use in children. Clinical trials are now being conducted to investigate the efficacy and safety of TpoR-As in pediatric ITP.